Creating Tourist Offers on the Basis of Anthropological Values. The Example of Gospodarstwo Edukacyjno-Agroturystyczne “Mazowiecki Zaścianek” - Klaudia Nowicka; Dominika Studzińska; Piotr Urbaszek (Barometr Regionalny, 2015)
The main goal of the paper is to assess the possibility of creating a successful tourist offer in areas which are not considered attractive for tourism. In order to do so, the authors analyze the case of an agrotourism farm called “Mazowiecki Zaścianek” which is located in the small Tłuszcz Commune west of Warsaw. The research carried out in 2013 was focused not only on the tourist product of the farm and its assessment, but also on ways in which the owners of the farms were able to enter a small community and stimulate its development.